Kesucian Mary Menurut Bible - Mohd Khambali @ Hambali, Khadijah Binti (Jurnal Usuluddin, 1998)
The word Virgin is always associated to Mary which known as the Virgin Mary and Virgin Mother of Jesus Christ. Thus, the concept of the Virgin is not known. Therefore, this article attempts to elaborate comprehensively the Virgin Mary based on scriptures and church's claims.